Green electrospun Manuka honey/silk fibroin fibrous matrices as potential wound dressing. (5th April 2017) - Yang, Xingxing; Fan, Linpeng; Ma, Linlin; Wang, Yunyi; Lin, Si; Yu, Fan; Pan, Xiaohan; Luo, Gejie; Zhang, Dongdong; Wang, Hongsheng
Abstract: Wound dressing plays an irreplaceable role in preventing infection and accelerating healing of wounds, especially the chronic non-healing wounds. Recently, the electrospun silk fibroin (SF) fibrous matrices is regarded as an ideal candidate for wound healing in virtue of its excellent skin affinity and good permeability for air and water. Manuka honey (MH) has demonstrated its unique properties in wound healing, including anti-inflammatory and anti-bacterial function as well as promoting tissue growth and reducing pain of patients. Here we report the feasibility of developing MH/SF composite fibrous matrices as antimicrobial wound dressing. SF fibrous matrices loading different amount of MH were manufactured by green electrospinning. The FTIR spectra indicated that MH was successfully loaded into the SF fibers. The composite fibers show smooth morphology and their diameter increases with MH content increased. Interestingly, the incorporation of MH significantly improved the antimicrobial activity of SF fibrous matrices, without negative effect on the excellent biocompatibility of SF. Moreover, the MH/SF composite fibrous matrices showed good performance on improving wound healing according to the data of animal experiment. Our findings suggest as-prepared natural green composite matrices combining the merits of both SF and MH could be a promising candidate for wound dressing. Highlights: Manuka honey/silk fibroin (MH/SF) fibrous matrices were prepared by green process. MH/SF fibrous matrices favor cell attachment and growth. MH/SF fibrous matrices demonstrated high antibacterial ability. MH/SF fibrous matrices showed good performance on improving wound healing. Graphical abstract: Schematic illustration for the fabrication of Manuka honey-loaded silk fibroin composite fibrous mats.